Reintubation Rate between Nasal High-Frequency Oscillatory Ventilation versus Synchronized Nasal Intermittent Positive Pressure Ventilation in Neonates: A Parallel Randomized Controlled Trial - Phatigomet, Manapat; Thatrimontrichai, Anucha; Maneenil, Gunlawadee; Dissaneevate, Supaporn; Janjindamai, Waricha (American Journal of Perinatology, 2023)
Objective Nasal high-frequency oscillatory ventilation (nHFOV) and synchronized nasal intermittent positive pressure ventilation (sNIPPV) were the new modes of noninvasive ventilation. This study's aim was to clarify as to which of the nHFOV and sNIPPV modes was superior in preventing postextubation failure or reintubation in neonates.Study Design An open-label parallel randomized study was performed. Extubated preterm and term neonates were randomly allocated into nHFOV or sNIPPV modes; the reintubation rate was evaluated within 7 days after extubation between the two modes. Subgroup analyses were performed for preterm (gestational age <37 weeks) and very preterm (gestational age <32 weeks) neonates. The sample calculation was 1,050 neonates; however, this trial was stopped early as enrollment was too slow.Results From July 2020 to June 2022, 202 neonates were assessed for eligibility and 69 neonates were excluded. Finally, 133 neonates were randomly allocated to the study interventions (nHFOV = 67, sNIPPV = 66). The median gestational age and birth weight were 33 (30–37) weeks and 1,910 (1,355–2,836) g, respectively. The reintubation rate within 7 days did not significantly differ between the groups (nHFOV [5/67, 7%] vs. sNIPPV [4/66, 6%]); risk difference [95% confidence interval] = 0.01 [−0.08 to 0.11]; p = 0.99), including preterm (nHFOV [4/55, 7%] vs. sNIPPV [3/44, 7%]) and very preterm (nHFOV [3/25, 12%] vs. sNIPPV [3/25, 12%]) neonates.Conclusion After neonatal extubation, there was no significant difference of reintubation rates within 7 days between nHFOV and sNIPPV. This trial has been registered in the ClinicalTrials.gov database (https://clinicaltrials.gov/ct2/show/NCT04323397). First posted registration on March 26, 2020.Key Points
Keywords: airway extubation; high-frequency ventilation; intermittent positive pressure ventilation; newborn; noninvasive ventilation; premature infant